Toll-like Receptor 3 (TLR3) Signaling Requires TLR4 Interactor with Leucine-rich Repeats (TRIL) - Carpenter, Susan (American Society for Biochemistry and Molecular Biology, 2011)
Toll-like receptors (TLRs) are a family of proteins that act as the primary sensors of microbial products. Many TLRs require accessory molecules in order to recognize these microbial products and initiate signal transduction cascades. We have identified TRIL (TLR4 interactor with leucine-rich repeats) as a novel modulator of TLR4 signaling showing high expression in the brain. We now show that TRIL also plays a role in TLR3 signaling. TRIL is expressed intracellularly in the astrocytoma cell line U373 and in the monocytic cell line THP1. TRIL co-localizes with the endosomal compartment. These data are consistent with a role for TRIL in TLR3 signaling and endosomal TLR4 signaling. TRIL was induced by the TLR3 ligand poly(I:C). Overexpression of TRIL enhanced cytokine production and interferon-stimulated response element (ISRE) luciferase activity following poly(I:C) stimulation in U373. TRIL interacted with TLR3, and this interaction was enhanced following poly(I:C) stimulation. Transient knockdown of TRIL with siRNA or stable knockdown using shRNA in U373 cells inhibited TLR3 signaling, reducing ISRE luciferase, RANTES, and type I interferon production. Knockdown of TRIL did not affect TLR2 signaling. Most accessory molecules identified to date, such as CD14, gp96, PRAT4a, and Unc93B, all play roles in multiple TLR signaling pathways, and we now show that this is also the case for TRIL.